2002
DOI: 10.1590/s1517-74912002000300009
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da nicotina na viabilidade e morfologia de fibroblastos: estudo in vitro

Abstract: The aim of this study was to evaluate, in vitro, the effect of nicotine on the viability and morphology of fibroblasts from a continuous lineage. Two experimental groups were prepared, with different drug dosages (0 - control, 10 microgram 100 microgram, 0.5 mg, 1 mg) and conditioning time (1 and 24 hours). Twelve-well microplates were utilized. Each well received 2 ml of fresh culture medium and 1 ml of a solution containing 1 x 10(5) cells/ml. Nicotine was then added to the wells, at the tested concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…According to some of these authors, fibroblasts exposed to nicotine undergo morphological alterations, principally cytoplasmic vacuolization. They become inactive and even unviable [11][12][13]17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some of these authors, fibroblasts exposed to nicotine undergo morphological alterations, principally cytoplasmic vacuolization. They become inactive and even unviable [11][12][13]17 .…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have reported cytoplasmatic modifications, degeneration and inactivity of fibroblasts [11][12][13] , in addition to a reduced number of these cells and their differentiation 11,12,[14][15][16][17] and deficiencies in collagen synthesis 11,13,15,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Os fibroblastos sofreriam tanto na sua estrutura 15-17 quanto na proliferação e diferenciação 13,15,16,[18][19][20] . Nestes estudos estão descritas deficiências da síntese do colágeno 15,17,18,22,23 .…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Fang e Svoboda, estudando fibroblastos humanos, cultivados com diferentes concentrações de nicotina, observaram que existia inibição da diferenciação dos fibroblastos a miofibroblastos e atribuíram a isto a diminuição da contração das feridas 14 . São relatadas modificações citoplasmáticas, degeneração e inatividade dos fibroblastos [15][16][17] , além da diminuição do número destas células e da sua diferenciação 13,15,16,[18][19][20] . Estes efeitos foram também descritos nos osteoblastos, afetando a reconstituição após fraturas 21 .…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…Quando ocorre corrosão, a lesão pode tanto ser superficial, quanto estendida aos tecidos mais profundos, formando assim uma porta de entrada para aquelas substâncias que antes não conseguia permear o extrato, exercerem efeitos sistêmicos deletérios, ou mesmo causar seus efeitos diretamente sobre as células, a citotoxidade (Singh e Singh, 2001;Oga, 2008). (Martinez et al, 2002;Nathalie et al, 2006), porém inúmeras alterações a nível metabólico também ocorrem, decorrente do desequilíbrio homeostásico ou modificações no código genético celular, alterações que podem ser avaliadas por diversas metodologias analíticas (Mosmann, 1983;Rogers e McDougal, 2002;OECD, 2004;Nathalie et al, 2006;Valadares et al, 2007).…”
Section: Toxicidadeunclassified